Aided modeling para ensino de linguagem e repertório verbal: análise conceitual a partir da análise do comportamento - Calfa, Ariana Pedornesi (2024)
This dissertation sought to interpret, conceptually, from the framework of behavior analysis, aided modeling for teaching verbal responses in AAC (Augmentative and Alternative Communication). Aided modeling is proposed for teaching verbal behavior and language to individuals with complex communication needs – including ASD – and consists of teaching based on observation of the relationships between what is said vocally, the visual stimulus pointed out and the context in which such a response was evoked. The description of the procedure analyzed was that of the PODD Introductory Workshop Manual by Porter (2017). This analysis resulted in the identification of four intervention steps: assessment, environmental planning, the formation of the verbal community and the presentation of models of verbal interactions and opportunities to respond. From the description of the stages, the concepts of verbal behavior and the conditions for the development of the speaker's repertoire from the listener's repertoire were recovered. The similarity of the procedure with SPOP (stimulus-paring observation procedure) was recognized, which enabled possible behavioralanalytic interpretations of AAC teaching, integrating concepts of observational learning, MEI (multiple-exemplar instruction), integration of listening and speaking repertoire to from BiN (bidirectional naming), emergence of responses, formation of equivalence classes, function transfer, modeling and incidental training. It was possible to recognize the importance of incidental training, natural reinforcers and non-intrusive prompts for teaching verbal behavior. Finally, based on studies in behavior analysis, possible methodological adjustments that could guarantee greater success in the acquisition of verbal repertoire from aided modeling were discussed, such as the assessment and training of pre-listener and listener skills, training sequence and early initiation of response and modeling opportunities